2018
DOI: 10.1002/jib.482
|View full text |Cite
|
Sign up to set email alerts
|

A study on malt modification, used as a tool to reduce levels of beer hordeins

Abstract: Storage proteins from barley, wheat and rye are toxic to gluten sensitive consumers. These consumers include those suffering from coeliac disease, which account for up to 1% of the global population, and non‐coeliac gluten sensitivity that may affect even greater numbers of the population. Codex Alimentarius has published guidelines and limits of gluten in gluten‐free foods, which are applied in Europe, and similar guidelines apply in the rest of the world. The storage proteins present in barley are hordeins. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 22 publications
0
3
0
Order By: Relevance
“…It was also reported that beer produced from malt germinated for 7 days had 44% reduced hordeins than that germinated for 3 days. Therefore, a significant impact of malting conditions was found on beer hordeins (Taylor et al., 2018).…”
Section: Grain: Structure and Morphophysiological Characteristicsmentioning
confidence: 99%
“…It was also reported that beer produced from malt germinated for 7 days had 44% reduced hordeins than that germinated for 3 days. Therefore, a significant impact of malting conditions was found on beer hordeins (Taylor et al., 2018).…”
Section: Grain: Structure and Morphophysiological Characteristicsmentioning
confidence: 99%
“…Beer production involves multiple steps where prolamins can be digested, degraded, or sequestered, including malting, mashing, filtering, fermenting, and stabilisation [30]. Remaining gluten concentrations are typically above CD regulatory thresholds [31], but can be decreased by using highly modified malt [32] or by using flocculating agents such as polyvinylpolypyrrolidone [30,33], silica gel, or tannins [34]. Alternatively, enzymes can be added [35] such as prolyl endopeptidases (PEPs) to digest proline-rich gluten proteins directly [36,37], or transglutaminase, which crosslinks dissolved proteins and facilitates their precipitation and removal [34,38].…”
Section: Introductionmentioning
confidence: 99%
“…According to Huang et al (2016), the activity of LD is increased during germination, and during mashing, it continues to convert dextrins into linear maltosachharides . Mashing temperature and pH are known to affect the activity of LD. …”
Section: Proteins In Barley Malt and Beermentioning
confidence: 99%